A multilevel examination of the relationship between role overload and employee subjective health: The buffering effect of support climates. Issue 2 (16th October 2017) - Alfes, Kerstin; Shantz, Amanda D.; Ritz, Adrian
Abstract : Although the belief that support alleviates the detrimental effect of job demands on employee health is intuitive, past research has produced an equivocal picture, requiring a renewed evaluation of this relationship. In the present study, we examine three sources of support (from the organization, leader, and team) that employees may draw from to reduce the negative effect of a specific job demand, that is, role overload. Unlike most prior research, we focus on these sources of support at the group level of analysis to determine the relative effectiveness of organizational support climate, leadership climate, and team climate as moderators of the role overload–subjective health relationship. Hierarchical linear modeling of data from 2, 288 employees nested in 132 workgroups in a state administration of Switzerland revealed that, after controlling for individual perceptions of support, team climate weakened the negative relationship between role overload and health. We did not find support for the buffering effect of organizational support or leadership climates. The article provides a nuanced test of the support‐buffering hypothesis by simultaneously exploring individual and group‐level sources of support and by demonstrating that some sources of support matter more than others in ameliorating the negative outcomes of role overload.